Rozmowy kontrolowane - Chęciński, Sylwester (Poland : Zespoły Filmowe Zodiak, 1991)
A continuation of the story of "Miś" and the first film that tried to look at the period of Martial Law with irony and without taking sides. The sports club manager Ochódzki is ordered to infiltrate the Solidarity movement. Armed with a photograph with Lech Wałęsa, Ochódzki sets off for provincial Suwałki. When Martial Law is declared, Ochódzki decides to go back to Warsaw. On the way he causes a car accident and continues his journey in a borrowed car. He is stopped by a police patrol who find Solidarity brochures in the car boot. Ochódzki tries to escape and by accident destroys the tank that is chasing him. This makes him into an undisputed Solidarity hero and one of the most wanted people in the country. The secret police officer who initially recruited Ochódźki now wants to eliminate him. Ochódźki must now flee for Sweden disguised as a woman. He does not do so, but succeeds in blowing up the Palace of Culture and Science – the symbol of communist power in Poland – by flushing the toilet.
Duration: 01:33:00
Keywords: Fiction films